The Determinants of Executive Compensation in US REITs: Performance vs. Corporate Governance Factors. Issue 4 (2nd October 2019) - Ascherl, Claudia; Schrand, Liesa; Schaefers, Wolfgang; Dermisi, Sofia
ABSTRACT: The paper examines whether executive compensation packages within the US REIT industry are determined merely by performance or also by CEO power mechanisms that have an essential influence on board-level negotiations. We offer original insights into management compensation arrangements during and after the financial crisis. The relative importance of cash bonuses in CEO compensation contracts has more than halved after the crisis. Simultaneously, after the financial crisis, equity-based compensation became increasingly important. Concerning the pay-for-performance link, our results show no relationship during the financial crisis. However, after the crisis, we find a strong significant link between remuneration packages and corporate success.